V17. Functional and structural neuroimaging of the human midbrain at 9, 4T. Issue 8 (August 2015) - Loureiro, J.; Hagberg, G.; Ethofer, T.; Erb, M.; Scheffler, K.; Himmelbach, M.
<x xml:space="preserve">Abstract</x> Introduction The SC (Fig. 1) consists of 7 layers and the most superficial layer receives input mainly from the retina. The intermediate layers contain neurons mostly involved in oculomotor control, and the deep layers contain multisensory and visuomotor neurons. In virtue of its small size and location deep in the brain there have been few studies of the SC in humans using fMRI (Linzenbold and Himmelbach, 2012). The great benefit of UHF is the increase in the blood oxygen level dependent size and the possibility to go for higher resolutions enabling to study layer specific function of the SC. In this study UHF 9, 4T MRI is used and the increase in sensitivity allowed us to get functional consistency across subjects on a short (10 min) stimulation paradigm (Duvernoy Atlas, 2009). Methods Functional measurements were conducted in 8 human healthy volunteers at the 9.4T scanner (Siemens) in Tübingen with a 31 channel head coil system (Shajan, 2013). A custom-built mirror and backprojection was used for visual stimulation. Left or right-sided half circles of a flickering checkerboard were shown in a block design interleaved with fixation baseline periods (15 s duration). For each subject two sessions of 10 min each were acquired (1 × 1 × 1 mm3, TR: 1 s, TE: 21 ms). The images were motion-corrected and smoothed with an isotropic 2 mm FWHM Gaussian kernel. For the subject-level GLM analysis the hemodynamic response was modified anticipating the delay of the response function relative to onset of 4 s (Wall, 2009). Activation maps were produced (Fig. 2). Regions-of-Interest (ROI) of the left and right SC were drawn manually for each subject. The created ROIs were shifted 1–5 mm in anterior and posterior direction generating 5 masks for each direction. By subtracting consecutive masks, we divided the SC in three zones that we called: superficial ROI zone(SZ), intermediate ROI zone (IZ), and deep ROI zone (DZ) (each ROI zone is comparable to the superficial, intermediate and deep layers of the SC, respectively). Averages of the beta estimates of the GLM model were calculated within each of these zones, for each subject and as a group. Results and discussion We were able to detect signal increases in the left and right SC in most of the subjects (Fig.1). We also found a lateralization of BOLD responses: right SC is activated when the left hemifield is stimulated (red) and vice versa (blue). As expected the highest signals were localized in the SZ of the SC for both right and left colliculi and for both right and left stimulation. We found this pattern not only in the group mean data but also in most individual datasets. It is also clear that the activations encountered in the SC are not present outside the structure, in the CSF, evidencing the localizing capacity of our technique. In the comparison between the left and right colliculi the combined effects of the SC anatomical layer structure and hemifield lateralization of signals became apparent (Fig. 2).